Pengaruh Pemberian Aspartam secara Oral terhadap Kadar AST dan ALT Serum serta Gambaran Histopatologi Hati Tikus Putih - Ros Sumarny; Sondang Khairani; Mohamad Rega Satria Ramadhan (Fakultas Farmasi Universitas Pancasila, 2020)
Aspartame is low calorie sweetener metabolized into aspartic acid, phenylalanine and methanol, methanol cause damage to the liver. The purpose this study to determine the effect rats of oral aspartame administration for 90 days on biochemical parameters AST, ALT and liver histopathology. Rats were divided randomly into four groups: normal control, dose groups 126, 252, 504 mg/kgBW. Blood samples were taken on the 0th, 30th, 60th and 90th days to measure AST, ALT levels and 90th day to see liver histopathology. AST and ALT measurements using UV-VIS spectrophotometry with a wavelength of 340 nm. The levels of AST and ALT on the 90th day in the normal group 41,55 and 48,40 UI/L. Dose groups 126, 252, and 504 mg / kgBW were low doses 54,62 and 57,72 UI/L, 66,88 and 70,47 UI/L, 77,50 and 80,03 UI/L. Rats histopathology liver of aspartame showed hemorrhage. Concluded aspartame can increase of AST and ALT levels in rats blood serum and liver damage.